KORELASI KESADARAN METAKOGNISI DENGAN HASIL BELAJAR MAHASISWA PADAMATA KULIAH METABOLISME DI PROGRAM STUDI PENDIDIKAN KIMIA UNIVERSITAS MUHAMMADIYAH PONTIANAK - Astuti Astuti; Dedeh Kurniasih; Rizmahardian Ashari Kurniawan (Universitas Muhammadiyah Pontianak, 2019)
This study was based on the observation results of students at Universitas Muhammadiyah Pontianak which showed that there was still lack of students’ metacognitive awareness. As a result, this study was intended to investigate the metacognitive awareness of students and its correlation to students’ learning outcomes on metabolism subject especially to chemical education students at Universitas Muhammadiyah Pontianak. The research method of this study was correlational descriptive method. Techniques of data collecting were direct communication and documentation. The subject of this study consisted of 15 students of chemistry students at Universitas Muhammadiyah Pontianak. The researcher modified metacognitive questionnaire developed by Schraw & Dennison (1994) as research instrument with observational sheet. This research was initiated by administering interview, distributing questionnaire and analyzing data. The research findings revealed students’ metacognitive awareness based on the observed indicators namely declarative knowledge 83,33%, conditional knowledge 72%, planning 50,67%, information management strategy 73.33%, understanding monitoring 72,38%, debugging strategy 81,33%, and learning evaluation 73,33%. The correlation between metacognitive awareness and students’ learning outcomes on metabolism subject at Chemical education Study Program Universitas Muhammadiyah Pontianak was interpreted as low as its correlation score was 0,128 due to lack of metacognitive awareness influenced students’ learning outcomes.